Impact of hydroxyurea therapy on clinicohematological parameters in children with sickle cell anemia - Nimisha Joshi; Nilesh Jain; Pramila Ramawat (Indian Journal of Child Health, 2021)
Background: Sickle cell anemia (SCA) is an autosomal recessive disorder associated with high morbidity and mortality in children. Hydroxyurea (HU) has shown to decrease the frequency of vaso-occlusive crisis, hospitalization, and blood transfusion in SCA patients. Objective: The objective of the study was to evaluate the efficacy of HU on clinical and hematological parameters in pediatric patients with SCA. Materials and Methods: A prospective analytic study was conducted among 49 children aged between 5 and 14 years, diagnosed with SCA visiting the outpatient department at a tertiary care center of Central India for over a period of 13 months. Children enrolled in the study were given HU and they were followed at every 2-month for 6 months. Clinical and laboratory parameters of the study population were recorded and analyzed. With nine children lost to follow up, the final analysis was carried in only 40 patients. Results: Most of the children (60%) belonged to the age group of 5–9 years and male predominance (70%) was observed in the study. Clinical parameters including number of hospitalization, vaso-occlusive crisis, and frequency of blood transfusion decreased significantly (p<0.01). After 6 months of HU therapy, there was increase in hemoglobin levels (p=0.002), decrease in total leukocyte count (p=0.001), and platelet count was observed (p=0.283). Improvement in the serum glutamic pyruvic transaminase and serum creatinine (p<0.01), serum bilirubin, blood urea, and serum glutamic-oxaloacetic transaminase (p>0.05) was observed. No adverse reactions were noticed during this study period. Conclusion: HU is an effective drug and can be safely used for the treatment in SCA.